Penyuluhan Gemar Dan Manfaat Konsumsi Ikan Di SMA Negeri 1 Sambas Kabupaten Sambas: Counseling of Gemar and Benefits of Fish Consumption in SMA Negeri 1 Sambas, Sambas Regency - Ridwan; Ari Saputra; Fitriyandi; Tety Tiara (Pakis Journal Institute, 2022)
Optimal and good growth and development of the child requires proper nutrition. Riskesdas found that 30.7% of children of this age were stunted, 18.4% were short, and 12.3% were very short. Fish protein is higher than beef, chicken and other meats in terms of quantity. Fish have higher levels of omega-3 fatty acids than other animal sources. Fish also has a good content such as protein. The purpose of this counseling is to provide students with an understanding of the importance of eating fish at SMA Negeri 1 Sambas, Sambas District, Sambas Regency. The approach used is to use the method of material exposure and evaluation. The counseling activities went smoothly, judging from the enthusiasm and enthusiasm of the students participating in the counseling activities. The results of the counseling showed an increase in students' knowledge about the love of eating fish and the benefits of eating fish in everyday life